The Impact of The Serasi Program Application on The Planting Index and Farming Income in The Banyuasin District - Lestina, Maya; Mulyana, Andy; Wulan Sari, Dwi (Journal of World Science, 2022)
Introduction: The match program is a swampland management program to increase food production and farmer welfare with the performance target of increasing tidal swamplands' planting index and productivity. This study aims to analyze the impact of implementing the SERASI program by comparing the cropping index, productivity and farm income before and during the implementation of the SERASI program. Methods: This study uses a type of quantitative research. The sample used the solving formula and obtained a random sample of 2522 people. The data were processed and tested statistically using the Paired T-test and the Independent T-Test in the SPSS version 26.0 program. Result: Research conducted in Banyuasin Regency in 2 (two) sub-districts, namely Tanjung Lago District and Muara Telang District, gave results based on the T-test, there was an increase in the planting index of 20.1728%, an increase in the productivity of rice planting season I (MT I) of 12.981%, increased productivity of rice planting season II (MT) by 8.257% and increased productivity of corn by 7.248%, and there was an increase in farmers' income from rice and corn farming by 31.458% when implementing the matching program. Conclusion: The productivity of MT I rice farming is higher when the program is compatible with an increase of 12.981%, the productivity of MT II rice farming is higher when the program is compatible with an increase of 8.267%, the productivity of corn farming is higher when the program is compatible with an increase of 7.248%. (3) Farmers' income from rice and corn farming is higher when the program is compatible, with an increase of 31.498%.